2020
DOI: 10.5039/agraria.v15i4a8576
|View full text |Cite
|
Sign up to set email alerts
|

Biomass production and macronutrient content in Pennisetum glaucum (L.) R. Brown as affected by organic fertilization and irrigation

Abstract: Given the growing and needing for more effective organic fertilization and irrigation on pearl millet cultivated in Brazilian semi-arid, a field experiment was conducted in 2012 and 2013 simulating the smallholder farming system adopted in the Brazilian semi-arid to explore the effect of five organic sources (bovine manure, goat manure, compost, green manure, and control) under irrigation and no irrigation conditions. The experiment was a fully factorial design with four replications. The highest values of sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
0
0
4

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 18 publications
1
0
0
4
Order By: Relevance
“…However, considering the costs related to each management, the use of organic residue practices alone is supposed to be low cost. These results agree with previous study carried out by Souza et al [38] and Vital et al [39] that reported high costs with the continuous use of organic fertilization following a combined strategy to add organic residues into a soil profile. These authors have reported plant and soil improvements (e.g., yield, and soil organic carbon content, respectively) with the continuous use of farmyard manure (10 t ha −1 ) in a tropical Ferralsol.…”
Section: Discussionsupporting
confidence: 93%
“…However, considering the costs related to each management, the use of organic residue practices alone is supposed to be low cost. These results agree with previous study carried out by Souza et al [38] and Vital et al [39] that reported high costs with the continuous use of organic fertilization following a combined strategy to add organic residues into a soil profile. These authors have reported plant and soil improvements (e.g., yield, and soil organic carbon content, respectively) with the continuous use of farmyard manure (10 t ha −1 ) in a tropical Ferralsol.…”
Section: Discussionsupporting
confidence: 93%
“…Dentre os métodos não destrutivos (indiretos), destacam-se aqueles obtidos a partir das dimensões das barras foliares, onde apresentam facilidades de uso, baixo custo e podem fornecer estimativas precisas durante o ciclo da planta, pois reduzem a variabilidade associada a procedimentos de amostragem, visto que utilizam apenas medidas de fácil obtenção na planta, tais como comprimento e largura com a geração de modelos matemáticos que permitem a previsão da área foliar. Além disso, tem o potencial de realizar experimentos de fenotipagem de plantas em larga escala e alto rendimento (MALDANER et al, 2009;SOUZA et al, 2014;SILVA, 2020;HATI e SINGH, 2021).…”
Section: Métodos De Medição De áRea Foliarunclassified
“…O experimento foi conduzido no período de fevereiro à maio de 2022, na Fazenda Experimental do Centro de Desenvolvimento Sustentável do Semiárido (CDSA) da Universidade Federal de Campina Grande (UFCG), localizado no município de Sumé -PB, nas coordenadas de Latitude 7°39'42.9"S; Longitude 36°53'41.8"W W e altitude de 518 m acima do nível do mar. O clima local, segundo a classificação de Köppen-Geiger, é do tipo Bsh' (semiárido quente), com temperatura média anual de 26 °C e precipitação pluviométrica média anual de 600 mm (VITAL et al, 2020). Em relação a sua demarcação, distribuição e semeadura, cada parcela foi formada por três linhas de 2,0 m de comprimento, espaçadas de 0,5 m, com área da parcela de 5 m 2 e total de 25 m 2 .…”
Section: Caracterização Da áRea Experimentalunclassified
“…Apresenta-se como uma planta herbácea anual com a arquitetura bastante variada O clima local, segundo a classificação de Köppen-Geiger, é do tipo Bsh' (semiárido quente), com temperatura média anual de 26 °C e precipitação pluviométrica média anual de 600 mm (VITAL et al, 2020). Durante o cultivo, dados meteorológicos foram coletados de uma estação agrometeorológica automática instalada próximo da área, cujos resultados médios diários estão descritos a seguir: precipitação total 2,31 mm; temperatura máxima 31,22 ºC; temperatura média 24,95 ºC; temperatura mínima 19,63 ºC; umidade relativa do ar 73,05%; umidade relativa do ar mínima 70,39%; e velocidade do vento 1,91 m s -1 .…”
Section: Morfologia E Fenologia Do Feijão-caupiunclassified